TRANSFORMASI LITERASI AI DALAM PENDIDIKAN AGAMA ISLAM MENUJU MODEL PEMBELAJARAN ETIS DAN TERBUKA DI ERA DIGITAL - Satria Kharimul Qolbi; Lola Fadilah; Dinda Amanda Ainun Nuzul; Muhamad Arif Nugraha (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to the world of education, including Islamic Religious Education (PAI), which now faces the challenge of preserving spiritual values amid the dominance of digital technology. This study aims to analyze and formulate a conceptual framework for the transformation of AI literacy in Islamic education toward an ethical and open learning model in the digital era. The research employs a qualitative approach using library research, analyzed through Miles and Huberman’s interactive model, which includes data reduction, data presentation, and conclusion drawing using source and theory triangulation techniques. The findings reveal that the integration of AI in PAI not only serves to enhance learning efficiency but also functions as a means of strengthening moral values, digital etiquette, and spiritual awareness. This transformation results in a learning model that positions teachers as value facilitators, students as active interpreters, and emphasizes the balance between technological intelligence and humanity. In conclusion, AI literacy in Islamic education plays a crucial role in nurturing a civilized, critical, and responsible generation, although this study remains conceptual and requires further empirical validation in real learning contexts